2011
DOI: 10.1080/00028487.2011.564069
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Fish Assemblage Structure in Northwestern Great Plains Streams

Abstract: Prairie streams are known for their harsh and stochastic physical conditions, and the fish assemblages therein have been shown to be temporally variable. We assessed the spatial and temporal variation in fish assemblage structure in five intermittent, adventitious northwestern Great Plains streams representing a gradient of watershed areas. Fish assemblages and abiotic conditions varied more spatially than temporally. The most important variables explaining fish assemblage structure were longitudinal position … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Li et al (2012) found a significant temporal fish assemblage change between January and May, and between May and July. Seasonal variability in fish assemblages has been often attributed to the species reproduction and spawning migrations (Gorman, 1986;Simier et al, 2004;Arceo-Carranza & Vega-Cendejas, 2009;Mullen et al, 2011) or seasonal changes in physical conditions of river ecosystems (Mullen et al, 2011). In our system, reproductive migration could be an important reason to explain the temporal variability.…”
Section: Temporal Variation Of Fish Assemblagesmentioning
confidence: 95%
See 2 more Smart Citations
“…Li et al (2012) found a significant temporal fish assemblage change between January and May, and between May and July. Seasonal variability in fish assemblages has been often attributed to the species reproduction and spawning migrations (Gorman, 1986;Simier et al, 2004;Arceo-Carranza & Vega-Cendejas, 2009;Mullen et al, 2011) or seasonal changes in physical conditions of river ecosystems (Mullen et al, 2011). In our system, reproductive migration could be an important reason to explain the temporal variability.…”
Section: Temporal Variation Of Fish Assemblagesmentioning
confidence: 95%
“…For example, the environmental variables differed between high and low flow seasons in coastal rivers of the Andalien drainage as well as Meridional Amazonian streams in the Neotropics, while the fish assemblage compositions did not differ between two seasons (Habit et al, 2007;Fernandes et al, 2013). Spatial variation exceeded temporal variation in fish assemblages in five northwestern Great Plains streams and the Upper Mississippi River System (Mullen et al, 2011). In such case, local fish fauna and life history traits of species (e.g., migration, production, feeding) might play an important role in temporal trends in assemblage composition.…”
Section: Temporal Variation Of Fish Assemblagesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Mullen et al . () found that four samples spread across seasons are sometimes needed to detect all of the fishes that occur at a particular site in prairie streams. Inclusion of temporal variability in fish assemblages and habitat conditions or detection probability in species‐habitat models has been suggested by other authors to improve accuracy (Wiley et al ., ; Hayer et al ., ; Steen et al ., ; Falke et al ., ) and may have improved the number of significant reach and catchment‐scale models in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Matthews () in a study of fish communities in riffle habitats of the Roanoke River, Virginia, U.S.A., and Mullen et al . () in a study of Montana prairie streams, however, have both found that spatial variation in fish assemblages was greater than temporal variation. Furthermore, Shearer & Berry () found long‐term persistence of most native prairie fishes between dry and wet periods due to the tolerance of these species to variable physicochemical conditions, and Matthews & Marsh‐Matthews () found that the influences of drought on fish assemblages in prairie streams of Oklahoma, U.S.A., may be short lived as recolonizations of fishes may be rapid during improved conditions.…”
Section: Discussionmentioning
confidence: 99%